1996
DOI: 10.1103/physrevlett.77.1881
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Intrachain Exciton Generation and Decay in Poly(p-phenylenevinylene)

Abstract: We present excitation spectra, picosecond decay time, and quantum efficiency measurements of the photoluminescence (PL) signal in poly(p-phenylenevinylene) (PPV). In pristine PPV we observe a constant efficiency with excitation wavelength for singlet intrachain exciton generation, which we model to be close to unity. In contrast, photo-oxidized PPV samples contain a distribution of quenching centers following the profile of the absorption depth, which causes the PL efficiency to decrease with increasing excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(74 citation statements)
references
References 36 publications
5
65
0
2
Order By: Relevance
“…As mentioned in the Introduction, several groups have argued that photooxidation of conjugated polymer films can take place quite readily, even at relatively low excitation intensities. 39,40,49,74,75 The photophysical signatures of oxidative damage are a reduced PL quantum yield and the appearance of an excited-state absorption in the spectral region where SE is expected to occur. One suggestion for reducing photodamage is to excite the polymer film through the transparent substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the Introduction, several groups have argued that photooxidation of conjugated polymer films can take place quite readily, even at relatively low excitation intensities. 39,40,49,74,75 The photophysical signatures of oxidative damage are a reduced PL quantum yield and the appearance of an excited-state absorption in the spectral region where SE is expected to occur. One suggestion for reducing photodamage is to excite the polymer film through the transparent substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported a link between photooxidation and reduced PL quantum yield. [74][75][76] Several groups also have argued that irreversible photodamage can occur in conjugated polymer samples at relatively low (e10 18 cm -3 ) excitation intensities, 39,49 even in the vacuum of a cryostat. 40 The chief signature of photochemical damage is a rapid decay of SE and the appearance of PA in the emission region; the PA in the near-infrared is only slightly affected.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, exciton-exciton annihilation [30], generating free charges, may explain the small real component of the slowly decaying conductivity in Fig. 2(b).…”
mentioning
confidence: 99%
“…As the oxidation is not oxygen limited, the film is not uniformly oxidized. A carbonyl concentration profile is formed [7] following the laser intensity decay in accordance with the Beer-Lambert law. As a consequence of chain shortening process, an inhomogeneous profile of PPV segments of different sizes is continuously generated from the interface air/polymer into the film.…”
Section: Methodsmentioning
confidence: 99%
“…Models of photoluminescence (PL) decay dynamics [1,5,6] and photoluminescence excitation spectroscopy (PLE) [2,[7][8][9] reveal details of carrier dynamics, quenching mechanisms and oxidation processes. The quenching process was accounted by attributing an additional non radiative decay channel to excitons [1][2][3][4][5][6][7]. This effect has been ascribed to the creation of carbonyl groups.…”
Section: Introductionmentioning
confidence: 99%